2022
DOI: 10.1007/s00429-022-02557-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional MRI evidence for significant contribution of precentral gyrus to flexible oculomotor control: evidence from the antisaccade task

Abstract: Antisaccade task requires inhibition of a prepotent prosaccade to a peripheral target and initiation of a saccade to the opposite location, and, therefore, is used as a tool to investigate behavioral adjustment. The frontal and parietal cortices are both known for their activation during saccade generation, but it is unclear whether their neuroanatomical characteristics also contribute to antisaccades. Here, we took antisaccade cost (antisaccade latency minus prosaccade latency) as an index for additional time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Aberrant functional connectivity between the PreCG and left anterior insula was associated with processing of stressful experiences (Goodman et al, 2022). According to our research, the left PreCG was functionally implicated in saccade execution and may play a role in determining an individual's antisaccade cost (Jin et al, 2022). This study also investigated the feasibility of PSS method in differentiation of abnormal spontaneous activity of brain in AUD patients from healthy volunteers.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Aberrant functional connectivity between the PreCG and left anterior insula was associated with processing of stressful experiences (Goodman et al, 2022). According to our research, the left PreCG was functionally implicated in saccade execution and may play a role in determining an individual's antisaccade cost (Jin et al, 2022). This study also investigated the feasibility of PSS method in differentiation of abnormal spontaneous activity of brain in AUD patients from healthy volunteers.…”
Section: Discussionmentioning
confidence: 67%
“…Aberrant functional connectivity between the PreCG and left anterior insula was associated with processing of stressful experiences ( Goodman et al, 2022 ). According to our research, the left PreCG was functionally implicated in saccade execution and may play a role in determining an individual’s antisaccade cost ( Jin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…The increased strength of the FC of the ACC-iLOC and InsulaR-PreCGl in the experimental group suggested that the intervention enhanced the ability to inhibit negative stimuli and that empathy and acceptance reduced emotional responses to negative stimuli. This may be because the precentral gyrus, as the primary motor cortex, controls the voluntary motor ( Jin et al, 2022 ), which may be associated with executive response inhibition. And the InsulaR and ACC are activated by empathy ( Hein et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%